"Programa LEM: Tocar e Cantar": um estudo acerca de sua inserção no processo músico-formativo de unidocentes da Pedagogia/UFSM - Correa, Aruna Noal (2008)
This dissertation is linked to the research line Education the Arts from the PPGE/UFSM and the group of studies and research in Training, Action and Research in Musical Education - FAPEM. Aimed to investigate the "Program LEM: Playing and Singing", in the form of music workshops, seeking to emphasize its contributions in the formation of musical training and teaching-musical by students and former students of Pedagogy/UFSM, which are called up workshopers . Specifically, it is sought to know their ideas about the workshops for the musical and pedagogicmusical development of unidocent teachers, identify the contributions of workshops for the musical and pedagogic-musical development of unidocent teachers, and also map the musical and teaching-music training some needs raised to unidocency. As a methodological approach, the qualitative research was chosen mainly on the basis of the analysis of contexts and realities experienced by eight workshopers subjects of the research. A semi-structured interview was the main tool for collecting data, being divided into two stages: the first, a semi-structured individual interview (EI) and the second, with the completion of an interview in a group (EG). The theoretical reference was built from two subjects: the training of teachers, and the relationship between music education and unidocency, and workshops on music, which presents a brief history of its existence in the country as well as the formation of the "Program LEM: Playing and Singing" at UFSM. Data analysis was divided into crossing between the relationship of workshops with the Program, the workshops and training in Pedagogy, and following, it was sought to make up relations between the unidocent training, the musical education, and the educational practice developed by the workshopers. As a conclusion of this research, there is the "Program LEM: Playing and Singing" as a musical training space-relevant in the initial training of teachers, contributing to the unidocents have more alternatives of work and assurance when working with music in school. Still, it is pointed out that initiatives like this should be encouraged in unidocent forming.